COPD biomarkers as tools for decision making in early clinical drug development. (May 2016) - Taib, Ziad; Jauhiainen, Alexandra
In this perspective article, we discuss, from a statistician's perspective, how biomarkers can be useful in decision making in drug development with emphasis on early clinical development (Phase I and II) in chronic obstructive pulmonary disease. We illustrate with examples of how biomarkers can affect the very choice of treatment strategy: for example, targeting patients in early versus late phases of the disease or patients with particular extrapulmonary manifestations of chronic obstructive pulmonary disease. We also illustrate the use of biomarkers for establishing proof of mechanism in Phase I trials and how surrogate biomarkers can be used as end points in Phase II leading to shorter and more efficient proof-of-principle and dose-finding trials.